Hubungan Antara Kedisiplinan Belajar dengan Hasil Belajar Fikih Siswa Kelas XI MAN 1 Kabupaten Bogor - Salma Aisyah; Sri Nurul Milla; H. Ikhwan Hamdani (PKP Pusat Jurnal LPPM IAi Nasional Laaroiba, 2024)
Discipline has an important role in the educational process, shaping behavior in accordance with the values taught, and influencing learning outcomes. Student indiscipline, such as tardiness, assignments that are not on time, and violations of school rules, can hinder the learning process and create a less conducive learning environment. This research uses a quantitative type of approach. This research uses a descriptive method. The variables used in this research are learning discipline (independent variable) and fiqh learning outcomes (dependent variable). The aim of this research is to find the relationship between learning discipline and the fiqh learning achievement of class XI students at MAN 1 Bogor Regency using quantitative correlational research methods. The level of learning discipline of class XI MAN 1 Bogor Regency students is sufficient, with an average score of 52.2. The level of fiqh learning outcomes for students in class XI MAN 1 Bogor Regency is medium, with an average score of 77.88. There is a positive and significant relationship between learning discipline and the fiqh learning outcomes of class XI MAN 1 Bogor Regency students. Students' learning discipline has a real influence on their fiqh learning outcomes at MAN 1 Bogor Regency. In other words, the better the students' learning discipline, the better their fiqh learning achievements, and vice versa.